2022
DOI: 10.3389/fendo.2022.886085
|View full text |Cite
|
Sign up to set email alerts
|

LPS-Induced Systemic Inflammation Caused mPOA-FSH/LH Disturbance and Impaired Testicular Function

Abstract: Male reproductive function is key to the continuation of species and is under sophisticated regulation, challenged by various stressors including inflammation. In the lipopolysaccharide (LPS) intraperitoneal injection-induced acute systemic inflammation, male fecundity was compromised with decreased testosterone level, damaged spermatogenesis, and downregulations of testicular gene expression levels involved in steroidogenesis regulation and blood–testis barrier. It is also noteworthy that the testis is more s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 65 publications
2
9
0
Order By: Relevance
“…Acute LPS was demonstrated to suppress the HPG axis through impacts on the hypothalamus, and serum LH was found to decrease consistently across various animal models including rats, mice, monkeys, and ewes, despite differences in LPS serotypes and sources ( 4 , 40 42 ). Some recent studies show increase of serum FSH similar to our study in response to LPS in male mice ( 43 ), laying geese ( 10 ), and ewes( 44 ) with implications for activation upstream of the pituitary, though the time frames were limited to acute or less than a week.…”
Section: Discussionsupporting
confidence: 84%
“…Acute LPS was demonstrated to suppress the HPG axis through impacts on the hypothalamus, and serum LH was found to decrease consistently across various animal models including rats, mice, monkeys, and ewes, despite differences in LPS serotypes and sources ( 4 , 40 42 ). Some recent studies show increase of serum FSH similar to our study in response to LPS in male mice ( 43 ), laying geese ( 10 ), and ewes( 44 ) with implications for activation upstream of the pituitary, though the time frames were limited to acute or less than a week.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, Zheng et al directly observed that macrophages and dendritic cells capture spermatozoa in the caudal cavity of the epididymis for the first time, directly proving that chronic epididymitis is a possible cause of oligospermia in patients (Zheng et al, 2021). We suggest that one of the potential reasons for the association between gut microbiota and male infertility is elevated LPS, which can result in local testicular inflammation and oxidative stress disorders, and does harm to the normal testicular structure such as the BTB (Shen et al, 2022).…”
Section: Gut Microbiota Disrupt the Testicular Structurementioning
confidence: 68%
“…The detrimental impact of the gut microbiota on BTB can be partially ascribed to inflammation and oxidation, mainly caused by LPS. A study found that LPS treatment can lead to orchitis and significantly decrease the expression of cell junctions, such as testicular intercellular adhesion molecule 1, tight junction protein 1, and gap junction α-1 protein (Shen et al, 2022). Furthermore, IL-6, induced by gut microbiota, can damage the tight junctions of Sertoli cells by disrupting the ERK-MAPK signaling pathway and changing the localization and number of BTB component proteins (Zhang et al, 2014).…”
Section: Gut Microbiota Damage Btbmentioning
confidence: 99%
“…Consistent with this hypothesis, our results showed that the defects in the intestinal mucus barrier can also increase serum LPS levels. It has been found that the intraperitoneal injection of LPS could induce dysfunction of the testis and epididymis and significantly reduce serum testosterone levels via induction systemic inflammation ( 48 , 49 ). Besides, LPS could directly induce pyroptosis of Leydig cells and decrease testosterone production ( 50 ).…”
Section: Discussionmentioning
confidence: 99%